Evaluasi Tim Renang Kota Mojokerto Dalam Mengikuti Kejuaraan Daerah Renang Jawa Timur Tahun 2023 - Muhammad Zailul Rizky; Mokhamad Nur Bawono (Pusat Riset dan Inovasi Nasional, 2024)
Sport is a physical activity needed by humans which has many purposes, such as maintaining body health, maintaining mental health (refreshing), achieving achievements, building character and other people (Wijaya, 2018). According to Kurt et al., (2023) swimming is a sport that can be used as a means of talent search, achievement, recreation, education, rehabilitation and self-preservation. Coaches, facilities and infrastructure, training programs, athlete development, government support and parents are some of the components that contribute to good performance. Sports achievements can be achieved through professional and quality sports training. In the sport of swimming, there are several events, namely events representing clubs, events representing regions at the provincial level, events representing regions at the national level, and events representing international national levels. The process of improving actions or techniques that have been carried out is known as evaluation. This research is motivated by the fact that there is still no research on the Mojokerto City swimming team in participating in the 2023 East Java Regional Swimming Championship. This research aims to cycle the Mojokerto City swimming team in participating in the 2023 East Java Regional Swimming Championship. The use of the SWOT method is important in analyzing and determining points earned. This method focuses on evaluating the Mojokerto City swimming team in participating in the 2023 Regional Swimming Championships which is expected to contribute to achievements for the City of Mojokerto in the future. To explain the evaluation results, the methodology used is qualitative descriptive research. The source of information comes from licensed swimming coaches. Data collection methods include interviews and documentation. Research findings include, (1) strengths include: the Mojokerto City swimming team is in young athletes and young coaches. If young athletes are coached properly, they will develop, while young coaches who are full of ideas, if given space or a platform, can express their aspirations. (2) Weaknesses include: no management questions, no atlhletes selection, no impressive Training Center (TC), no space or forum for young coaches to express their aspirations. (3) Opportunities include: the Mojokerto City swimming team has good opportunities for the future because this team is dominated by young athletes and young coaches. (4) Threats include: if the existing management is not immediately improved, the young athletes and young coaches, the Mojokerto City swimming team is threatened with not being able to get maximum results in future events.